2006
DOI: 10.1111/j.1442-2018.2006.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe occupational injuries among older workers: Demographic factors, time of injury, place and mechanism of injury, length of stay, and cost data

Abstract: Between 2002 and 2012, the number of individuals > 55 years of age in the workforce is projected to climb by approximately 50%. Few studies have substantiated that severe occupational injury to older workers is a significant problem. To identify the variables related to traumatic injuries of older workers, data were abstracted retrospectively from a regional trauma center database, including demographic and injury characteristics, length of hospital and intensive care unit (ICU) stay, and cost. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Susceptibility to occupational injuries may increase with age but decrease with work experience. Our data showed that the odds of minor and OSHA recordable injuries increased with age, which is consistent with previous findings that if injured, older workers tend to experience higher severity injuries and have higher fatality rates than younger workers [Grandjean et al, 2006]. The main objective of this investigation was to determine the impact of a NM reporting system on the rate of minor and OSHA recordable injuries.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Susceptibility to occupational injuries may increase with age but decrease with work experience. Our data showed that the odds of minor and OSHA recordable injuries increased with age, which is consistent with previous findings that if injured, older workers tend to experience higher severity injuries and have higher fatality rates than younger workers [Grandjean et al, 2006]. The main objective of this investigation was to determine the impact of a NM reporting system on the rate of minor and OSHA recordable injuries.…”
Section: Discussionsupporting
confidence: 90%
“…Since age and job experience may be associated with injury rates, we included age and duration of employment in analyses. Older workers are at higher risk of occupational injuries, and injuries experienced by older and more experienced workers tend to be more severe and require longer recovery times than injuries to younger and inexperienced workers [Pickett et al, 1999[Pickett et al, , 2001Solomon, 2002;Grandjean et al, 2006;King et al, 2009;Kucera et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…While workers aged 55 years and above experience more severe consequences as a result of injuries than their younger counterparts, the rates of non-fatal work-related injuries are lower among the older, compared to the younger group (Grandjean et al, 2006 ; Silverstein, 2008 ). As reported by the Bureau of Labor Statistics, work-related injuries resulted in over 1.1 million days-away-from-work cases in the year 2015 among the U.S. private industry and state and local governments.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the chance the injury will be severe in older workers is substantial. 30,31 There is a continuing increase in health care consumption by older Americans. One possible explanation is that there are substantial declines in health beginning at the age of 60 years.…”
Section: Discussionmentioning
confidence: 99%